A review of oil well cement alteration in CO2-rich environments. (20th October 2018) - Bagheri, Mohammadreza; Shariatipour, Seyed M.; Ganjian, Eshmaiel
Highlights: Formation of four main zones within the cement matrix. The residence time and the aperture size determine cracks' behaviour. A cement matrix is damaged more than its surrounding rock. Self-sealing behaviour is likely, when a well is properly cemented. Abstract: The purpose of this study is to examine previous works undertaken that characterise the cement alteration due to its exposure to CO2 -bearing fluids attacking on the interfaces of cement-rock and cement-casing, or through cement cracks, and the cement matrix itself. Numerous studies have reported carbonation of well cements. The majority of studies reported self-healing behaviour of cements cracks observed under general CO2 storage conditions. In addition, defective cement matrix and bonding between cement and casing were also found to be potential causes for leakage pathways. Albeit, severe conditions, such as high acidity degree of brine and high flow velocity, may negatively affect the self-healing behaviour of the cement.